맞춤형 농정 추진방안 연구 - 김정호 (한국농촌경제연구원, 2006)
The aim of the recent agricultural policies places a higher value on increase of farm income and development of rural areas than a role as a national food supply. The individual and discriminatory policy measures for each policy such as direct payments, off-farm income development, and social welfare services are required to achieve these policy objectives. Accordingly, the driving ways of the agricultural policies tend to transform from the top-down supporting programs to the cafeteria style programs selected directly by policy demanders. Under the current policy regime, The Korean government has a plan to promote 'Customized Agricultural Policies,' seeking an innovation in the implementations of agricultural policies. All farms are first classifies as a several farm typology and then some policy programs for each farm typology are provided as a menu form. On the basis of these policy menus, farmers select the suitable policy programs for themselves according to their development levels. For the basic typology, all farms are classified into specialized farms, semi-specialized farms, and midium sized farms by the growth levels of farming. As auxiliary typology, elderly farms and staring farms are separated by farmer age. Subsidiary farms and hobby farms are also divided by the composition of farm income. The index determining farm growth is defined as the equivalent farm size to be made attainable more than the average income of urban workers. A core of the 'Customized agricultural policies' is that farmers choose the suitable policies for themselves, thus policy scheme for each farm typology should be provided in advance. Specialized farms, having higher share of agricultural income, need a industrial policy that help strengthen their competitiveness. Further, once independent management is considerably accomplished, the graduation from the government support can be considered. The other side, elderly farms, having a limitation in their farming development, require the supporting programs for a soft retirement from farming and the welfare policies for security for the aged. Especially the introduction of special income subsidy, designed to support elderly farmers who devoted a lifetime to farm work, is needed. Policies for the subsidiary farms include the installation of joint marketing facilities and training programs for off-farm employment, assisting those farmers lead a security life rural areas. The customized agricultural policies focusing on policy beneficiaries' demands need to establish some principals ahead of a practical implementation. Those principals embrace a clarification of objective, a discrimination of policy measure, a exclusivity of target, an equity of policy application, and an independence of selection. For efficient propelling of the customized agricultural policies, required arrangements are as followings. First, a farm registration system as the groundwork should be built. Second, the former policy projects should be adjusted to customized policies, revising enforcement guidelines of agriculture and forestry. Specially it is necessary that insufficient welfare programs should be reinforced. Third, all kinds of loan projects should be combined into a synthetic fund, which is distributed for farm facilities, farm operating, and farm management stabilization. Forth, it is necessary that the executive organs taking full charge of the customized agricultural policies in both central and local government. Lastly, associated statistical data including individual farm information should be improved. As a detailed method, a combined control system, controlling consistently and synthetically essential information such as the farm registration list, the farmland register, and the supporting fund record, is proposed. Researchers: Jeong-Ho Kim, Soo-Suk Kim, Tae-Gon Kim, Dae-Shik Park, Hye-Jung Kang E-mail address: jhkim@krei.re.kr, soosuk@krei.re.kr, taegon@krei.re.kr, pds8382@krei.re.kr, kang@krei.re.kr